Hyaluronic acid drugs in the treatment of joint pathology (literature review) - Vyrva, Oleg; Ashukina, Nataliya (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
On the base of literature review the possibility of hyaluronic acid application in the treatment of patients with arthritis and diseases of joint adjacent tissues was assessed. hyaluronic acid is important component of joint tissues, provides its normal function. At arthritis changes appear normal concentration of hyaluronic acid and its molecular weight decreases, it can lead to the violation of structural and biomechanical joint properties. Increasing of the level of hyaluronic acid in the joint due to intraarticular injections can help to restore viscosity properties of synovial fluid, provides chondroprotective, anti-inflammatory and pain relief actions. The most studied mechanism of hyaluronic acid is its ability to connect with CD44, due to this interleikin 1β, 6 and 8, prostaglandin E2, metalloproteinase expression are suppressed. Hyaluronic acid promotes the synthesis of chondral matrix (proteoglycans and collagen), decreases the frequency of chondrocytes apoptosis. Ability of hyaluronic acid to activate the migration of slightly differentiated cells and proliferation of fibroblasts could use it for the treatment of joint pathology. The results of the most of the studies, systematic reviews and meta-analysis tell about positive clinical appliance of hyaluronic acid drugs in the treatment of arthritis of the I–III stages. But the efficacy of such medicines depends on its origin, molecular weight, elasticity and duration of treatment. New direction of intraarticular therapy is combination of hyaluronic acid with chondroitin sulfate, which provide symptomatic and chondromodification action. For the discovery of the full mechanism of influence further studies must be performed. Drugs Sertobec can be medical drugs for the treatment of patients with arthritis and diseases of joint adjacent tissues.